Graphene-based frequency-reconfigurable slot antenna with gain enhancement using integrated metasurface for terahertz applications - Al Gburi, Ahmed Jamal Abdullah; Megahed, Amany A.; Mousa, Marwa E.; Elabd, Rania H. (Springer Nature, 2025)
This paper presents a novel Frequency-Reconfigurable Slot Antenna (FRSA) designed for terahertz (THz) applications, enhanced through the integration of a metasurface reflector (MSR). The antenna structure is fabricated on a flexible polyimide substrate and achieves reconfigurability via eight graphene-based switches that dynamically control the surface impedance. A 5×5-unit cell metasurface, placed 205 μm beneath the antenna, is employed to improve the radiation characteristics. Parametric simulations reveal that the antenna can operate across ten distinct switching states, enabling resonant frequencies ranging from 0.885 THz to 1.53 THz. The integration of the MSR results in noticeable improvements in radiation efficiency (up to 98%) and gain (up to 9.9 dB), whereas maintaining effective impedance matching in all states. The proposed design demonstrates excellent potential for use in flexible, miniaturized, and high-performance THz communication systems, offering dynamic spectral adaptability and improved radiation performance through metasurface-assisted tuning.